Growth and production performance of Pacific white leg shrimp Litopenaeus vannamei (Boone, 1931) in low stocking short term farming in earthen pond conditions - Suresh Babu, P. P.; Razvi, S.S.H; Venugopal, G.; Ramireddy, P.; Murali Mohan, K.; Srinivasa Rao, P.; Patnaik, R.R.S.; Acharyulu, V.N; Ananthan, P. S. (Indian Journal of Fisheries, 2014)
Higher input costs involved in intensive farming of Litopenaeus vannamei drive back the small and marginal farmers from venturing into shrimp farming. The production potential and performance of the species was evaluated in low stocking short term farming in earthen pond conditions. Details from five crops with varying stocking densities, crop period and seasons were analysed to evaluate performance of the species. At higher stocking rates the shrimp yielded better production. The present report indicates better performance of the species in summer season. Interestingly all the observations point towards the fact that final harvest size depends on stocking density (SD), as well as days of culture (DOC) and it was observed that the minimum DOC to get a size of 20 g is around 80 days at SDs below 30 m-2. The economic returns increased with increase in SD and DOC. Overall results imply that at any given SD, the economic returns per kg will be minimal till 80 DOC (approximately 20 g harvestable size) at stocking density less than 30 m-2. The study confirms that for small and marginal farmers, L. vannamei farming can be made profitable at a shorter culture period (up to 80 days) adopting lower affordable stocking rates.